IMPROVING THE STUDENTS’ WRITING ABILITY THROUGH SOCIOGRAM IN WRITING DESCRIPTIVE TEXT TO THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 7 PALEMBANG - Destriana Rafika; Sherly Marliasari; Indah Windra Dwi DA (Journal of English Education, Literature and Linguistics, 2018)
This thesis entitled “Improving the Students’ Writing Ability through Sociogram in Writing Descriptive text to the Eighth Students of Junior High School 7 Palembang. The objective of this study is to find out whether sociogram is effective or not to improve the students’ writing ability of the eighth grade students of junior high school 7 Palembang in writing descriptive text. The problem of this study was “is it effective to improve the students’ writing ability of the eighth grade students of junior high school 7 Palembang by using sociogram in writing descriptive text?.” The writer used pre-experimental method one group design pre-test and post-test. The population of this study was all of the eighth grade students of junior high school 7 Palembang in academic year 2017/ 2018. The sample is one class (VIII.2) that consist of 37 students that chose by using cluster random sampling. In the result of the study, the average of students score in post-test was 82.4, it was highest than pre-test that was 67.8. In post-test the highest score was 89 and the lowest score was 78. To compare the students’ scores in pretest and posttest, paired t-test was used. And the result of paired t-test we found that, t-obtained was 26.6 and t-table was 1.68. It means that t-obtained was higher than t-table (27.317>1.688). And from the result of the interpretation above we can conclude that improving the students writing descriptive through sociogram was effective.